The Effect of Job Insecurity on Employee Wellbeing in Karawang Factory Employees During the Covid-19 Pandemic - Fuza Choerun Nisa; Endah Andriani Pratiwi (Universitas Muhammadiyah Banjarmasin, 2023)
In 2019 an outbreak of Covid-19 appeared in Indonesia, causing several companies in various cities, including the city of Karawang, to carry out several terminations of employment to several employees to save the company from bankruptcy and keep the company running as usual. However, doing this layoff makes several employees feel worried about the fate of their future work or can be referred to as job insecurity, when employees feel that their job insecurity is working under pressure, and it makes them not prosperous at work. The purpose of this study was to determine the effect of job insecurity on employee wellbeing in Karawang factory employees during the Covid-19 pandemic. The research was conducted using a quantitative method with an inductive approach. The sampling method used accidental sampling technique and obtained a sample of 100 employees who had worked at least 1 year during the Covid-19 pandemic in Karawang. The data obtained were processed using SPSS and using a simple linear regression test. The results of this study show that there is an effect of job insecurity on employee wellbeing of 40% for factory employees in Karawang during the Covid-19 pandemic. Job insecurity category is high at 65% and employee wellbeing is low at 85%.